The financial burden of injury at an elite South African football club during the 2021-2022 premier soccer league season - Coppin, Andrew (Department of Health and Rehabilitation Sciences, 2025)
We sought to determine the injury incidence, athlete exposure, days lost to injury (burden) and financial cost of injury at a high-level professional football team during the 11-month South African Premier Soccer League season of 2021-2022.